Self-Reported Burden in Elderly Patients With Localized Prostate Cancer Treated With Stereotactic Body Radiation Therapy (SBRT) - Aghdam, Nima; Pepin, Abigail; Carrasquilla, Michael; Johnson, Colin; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Lei, Siyuan; Collins, Brian T.; Kumar, Deepak; Suy, Simeng; Lynch, John; et al. (Frontiers in Oncology, 2020)
Purpose: Retaining quality of life in patients treated with SBRT for prostate cancer remains paramount. As such, balancing the benefits of treatment against the effects of therapy on patients is essential. The EORTC QLQ-ELD14 (ELD-14) is a validated questionnaire with a domain dedicated to burden of illness and treatment. This study reports trends in self-reported burden in patients with prostate cancer treated with SBRT and reveals convergence of self-reported burden with EPIC-26 scores. Methods: All patients ≥70 years old, with localized prostate cancer treated with SBRT +/- ADT at Medstar Georgetown University Hospital from 2013 to 2018 and had completed the ELD-14 were eligible for inclusion in this cross-sectional cohort study. Response to questions related to disease and treatment burden were dichotomized into two clinically relevant categories (“Not at All” and “A Little” vs. “Quite a Bit” and “Very Much”). Additional demographic features were derived from available medical records. A total of 111 patients (Median age of 74) responded to the ELD-14 questionnaire at onset of treatment and at the 2 year mark. Responses to EPIC questionnaires at matched follow-ups were scored and correlated with the self-reported burden domain of the ELD-14 using the Spearman correlation coefficient. Results: Number of patients reporting “Quite a Bit” or “Very Much” burden from prostate cancer was 7.8% prior to treatment and 8.6% at 24 months post-SBRT. This domain was highest at 1-month (9.4%) and at 12-months post-SBRT (10.2%). Patient reported treatment burden was found to converge well with individual domains of EPIC-26. Conclusions: This cross-sectional study suggests a minority of patients reported high burden from their clinically localized prostate cancer or from their treatment with SBRT. Self reported burden converged well with lower EPIC scores in multiple domains.